Wybrane „Wergiliana” w zbiorach kórnickich (Selected Works of Virgil in the Kórnik Library Collections) - Bering, Piotr (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
The main purpose of this paper is to present selected manuscripts and old prints containing Virgil’s poetic works preserved in the collections of the Kórnik Library. A luxurious parchment manuscript from 1466, probably written for King Matthias Corvinus of Hungary, and an old-print with commentaries by Philip Melanchthon from the end of the 16th century were selected for deeper analysis. The latter book is preserved in two separate volumes in different libraries, which provided an opportunity to compare the two. Some attention was paid to the old-print containing the Italian translation of the Aeneid.